2013
DOI: 10.7196/samj.6910
|View full text |Cite
|
Sign up to set email alerts
|

A decade of tobacco control: The South African case of politics, health policy, health promotion and behaviour change

Abstract: These surveys demonstrate that the comprehensive and inter-sectorial tobacco control health promotion strategies implemented in SA have led to a gradual reduction in cigarette use amongst school learners. Of concern, however, are the smaller reductions in smoking prevalence amongst girls and black learners and an increase in smoking prevalence from 2008 to 2011. Additional efforts, especially for girls, are needed to ensure continued reduction in smoking prevalence amongst SA youth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
115
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(129 citation statements)
references
References 4 publications
10
115
4
Order By: Relevance
“…This is the message from the study by Reddy et al [1] reported in this month's SAMJ. The data sustaining the message were drawn from four Global Youth Tobacco Surveys (GYTSs) conducted among nationally representative samples of South African (SA) school learners during 1999,2002,2008, and 2011.…”
mentioning
confidence: 60%
“…This is the message from the study by Reddy et al [1] reported in this month's SAMJ. The data sustaining the message were drawn from four Global Youth Tobacco Surveys (GYTSs) conducted among nationally representative samples of South African (SA) school learners during 1999,2002,2008, and 2011.…”
mentioning
confidence: 60%
“…1,16,21,31 Smoking is considered to be socially acceptable among men compared with women in the majority of South African communities, thus accounting for the higher prevalence of smoking recorded among men. 48,49 The prevalence of smoking was higher among participants who were never married compared with those who were married. Marriage often comes with responsibilities and married participants are more likely to be restricted in their ability to purchase cigarettes.…”
Section: Discussionmentioning
confidence: 99%
“…There is an increasing evidence-based consensus that policy on alcohol, tobacco, cannabis and other substances should move from the 'war on drugs' towards a science-based public health approach (as was successful locally in addressing tobacco use). [3] We agree that various substances differ in their associated costs and harms and that globally alcohol is a far more harmful substance than cannabis. [4] We also agree that an approach to substances that emphasises harm reduction and human rights is also key, and that new local policies and programmes are urgently needed, given the enormous burden of disease caused by alcohol, tobacco, cannabis and other substance use.…”
mentioning
confidence: 90%